2017
DOI: 10.1001/jamaoncol.2017.1023
|View full text |Cite
|
Sign up to set email alerts
|

Association of Previous Clinical Breast Examination With Reduced Delays and Earlier-Stage Breast Cancer Diagnosis Among Women in Peru

Abstract: In a population in which most breast cancers are self-detected, previous clinical breast examination was associated with shorter patient delay and earlier stage at breast cancer diagnosis. In regions of the world that lack mammographic screening, the routine use of clinical breast examination may provide a resource-appropriate strategy for improving breast cancer early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 8 publications
4
40
1
2
Order By: Relevance
“…42,43 Clinical breast examination has been associated with shorter delays to diagnosis and may also be of value as an educational tool for breast awareness in resource limited settings. 44 More advanced stage at diagnosis in recently pregnant women has been found internationally, 21,45,46 but this study is the first such report from SSA and was consistent across its countries. It may indicate a common hormonal-driver of proliferation and more diagnostic challenges within lactating breasts, or it may simply reflect greater time demands of raising infant children, as the majority were women who had given birth 2-3 years ago.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…42,43 Clinical breast examination has been associated with shorter delays to diagnosis and may also be of value as an educational tool for breast awareness in resource limited settings. 44 More advanced stage at diagnosis in recently pregnant women has been found internationally, 21,45,46 but this study is the first such report from SSA and was consistent across its countries. It may indicate a common hormonal-driver of proliferation and more diagnostic challenges within lactating breasts, or it may simply reflect greater time demands of raising infant children, as the majority were women who had given birth 2-3 years ago.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to increasing awareness in communities, awareness in health professionals has also been tackled in successful down‐staging interventions . Clinical breast examination has been associated with shorter delays to diagnosis and may also be of value as an educational tool for breast awareness in resource limited settings …”
Section: Discussionmentioning
confidence: 99%
“…Breast self-examination and clinical breast examination periodicity were not associated with a longer time interval to attend the first medical visit constrasting with previous studies 21,32,33 . Moreover, these practices are not recommended for breast cancer screening on recent national directive 4 .…”
Section: Discussionsupporting
confidence: 82%
“…A significant proportion of breast cancer in LMICs is diagnosed at an advanced stage (American Joint Committee on Cancer stage III or IV), ranging from 30% to 50% in Latin America to 75% in Sub‐Saharan Africa 5,6 . The great majority of these advanced cancers are initially detected by the patient herself based on changes that she appreciates as a lump, thickening, or other progressive change 7,8 . Once she presents to the health care system with signs and/or symptoms in the breast, diagnostic services need to be available such that a prompt and accurate diagnosis (benign vs malignant) can be provided.…”
Section: Implementation Phasesmentioning
confidence: 99%
“…Although the WHO does not recommend population‐based, organized screening with CBE in any resource setting, in the absence of well organized, mammogram‐based screening programs, CBE is considered a reasonable approach in a lower resource setting, provided it is evaluated in a research context 22 . A recent cross‐sectional study of women with newly diagnosed breast cancer in Peru 8 demonstrated that women who had undergone a previous CBE (unrelated to their current diagnosis) had shorter delays from symptom development to presentation and were more likely to be diagnosed with earlier stage disease (American Joint Committee on Cancer stages 0, I, and II) compared with women who had never had a CBE. This also suggests that CBE as part of comprehensive breast health awareness may have value in improving the opportunities for early diagnosis of a (potential) future breast cancer.…”
Section: Implementation Phasesmentioning
confidence: 99%